Cultural technology: A framework for marketing cultural exports – analysis of Hallyu (the Korean wave). Issue 1 (8th February 2016) - Chen, Steven
Abstract : Purpose: – The purpose of this paper is to outline a framework for marketing cultural goods (e.g. music) to global markets by examining modes of entry and positioning strategies used by media producers of the South Korean music industry. Design/methodology/approach: – An historic analysis was implemented to investigate the modalities and structures through which cultural products are produced and disseminated. Data for this study came from 314 articles collected fromwww.allkpop.com, a leading English-language, South Korean popular culture news site. Findings: – The cultural technology framework consists of the institutionalization of cultural technology, exportation of cultural content, collaborations with local talent, and joint ventures with local markets. Research limitations/implications: – The findings emerge from an analysis of South Korean popular music industries, and further research is needed to generalize the results across cultural industries. Practical implications: – The cultural technology framework can be applied to cultural industries such as music, film, comics, and art, where culture and language could be barriers to adoption. Originality/value: – This study outlines a framework for the modes of entry and positioning strategies of cultural goods (e.g. music) in international markets. Extant literature has examined global marketing from the purview of durable consumer goods and brands, with limited insights into cultural products. More broadly, this paper addresses the call for more qualitative inquiry into international marketing topics.